Uá¹¡IRUL TASYÄ«â€™U FI TAá¹£Ä«á¸¥UL HADÄ«á¹¡I: DURÄSATU â€˜AN TAá¹£Ä«á¸¥I ABÄ« â€˜ABDILLÄá¸¥IL HÄKIMIL NISÄBAWÄ« HADÄ«á¹¡IYYUL á¹ªÄ«RU WA MIN KUNTU MAULÄHU FIâ€™LIYYU MAULÄHU FÄ« KITÄBIL MUSTADRIKU â€˜ALA á¹¢Aá¸¥Ä«á¸¥Ä«NA - Gazali, Abdul Malik (Center for Research and Development of Religious Literature and Heritage, 2013)
-